دراسة تأثير غبار معمل إسمنت طرطوس في محتوى أوراق صنف الزيتون "الخضيري" من بعض العناصر الثقيلة (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
The aim of this study was to evaluate the pollution of some heavy metals (Fe، Zn، Mn،Cu، Pb، Ni) from Tartous Cement plant, on the Khodairy olive trees' leaves. Khodairy Olive is the most common variant in the area where the study was conducted. We collected samples of the Olive Trees' leaves from the East, and North sides of the plant at different distances from the plant (200 metres, 2 Kilometres, 6 kilometres). These samples were processed and analysed for the concentration of the above heavy metals, by using the atomic absorption spectrophotometer in the Laboratories of the Agriculture Faculty at Tishreen University, Lattakia. The results had shown that these heavy metals were present in the leaves at different concentrations, in descending order as follows (Cu, Pb, Mn, Zn, Fe, Ni). We also found the these elements were at highest concentration in the samples collected at 200 meters distance from all sides. The leaves collected from the area on the East side of the plant contained the highest concentration on these elements(Iron, Lead, Nickel). Nickel and Lead were found in a relatively higher concentration than the rest of the heavy metals we studied.This is probably a reflection of the involvement of these two elements in the cement manufacturing process and subsequently the spread of these by the air causing pollution. هدفت هذه الدراسة إلى تقييم التلوث الناتج عن غبار معمل إسمنت طرطوس من بعض العناصر الثقيلة (Fe،Zn، Mn، Cu، Pb، Ni) في أوراق صنف الزيتون “الخضيري” على اعتبار أنه النوع النباتي السائد في منطقة الدراسة. تم جمع عينات الأوراق المدروسة من الجهتين (الشرقية والشمالية)للمعمل وعلى مسافات مختلفة منه(200م، 2كم، 6كم)، تم تحضير وهضم العينات لتقدير محتواها من بعض العناصر الثقيلة باستخدام جهاز الامتصاص الذري في مخابر كلية الزراعة. أظهرت النتائج بأنترتيب تراكيز العناصر الثقيلة في أوراق صنف الزيتون “الخضيري “كانت كالتاليNi >Fe >Zn>Mn>Pb>Cu، مع الإشارة إلى أن التراكيز الأعظميةلبعض هذه العناصر(الحديد، الرصاص، المغنيز والزنك) وجدت في المواقع المحيطة بالمعمل من الاتجاهات الأربعة والتي تبعد عنه حوالي 200م، وبينت الدراسة بأن الجهة الشرقية للمعمل هي الأكثر عرضة للتلوث من حيث محتوى أوراقها من بعض العناصر الثقيلة (الحديد، الرصاص، النيكل)، كما تبين وجود عنصري الرصاص والنيكل  في أوراق الصنف المدروس بكميات عالية نسبيا، وقد يعود المحتوى العالي  للمعدنين السابقين في معظم المواقع المدروسة إلى ما يحمله الهواء من جزيئات المعادن الثقيلة الناتجة عن عملية تصنيع الإسمنت بمراحلها المختلفة، وبالتالي ترتبط الحالة السمية لبعض المعادن في أوراق الزيتون بالتلوث الجوي.